Les procédés métalinguistiques et la saisie du référent exotique. Le cas d’incompatibilité sémantico-référentielle - Afsaneh Pourmazaheri (Linguae &: Rivista di Lingue e Culture Moderne, 2017)
Which metalinguistic processes are used in a travel narrative, when the universe of reference (which serves as the referential framework experienced by the author-traveler) is fundamentally heterogeneous to the language of the author and to his readers? What does he do to name the referents which have not received a name in that language? This is an important question especially at the beginning of the nineteenth century when Orientalists began to take an interest in the East. The Western author feels a priori that his potential reader is capable of grasping the representations he transcribed of real referents of exotic character. However, the estimate made is false, resulting in a break in understanding on the reader’s side. This occurs especially when the textual referent moves away from the “real” referent. The cognitive and semantic-referential difference or approximation are analyzed in the case of unexplained foreign words, using the strategies implemented by the author that we will discuss. For us, it is a question of studying, from a semantico-discursive perspective, the different processes that allow the writer to describe the exotic referent, starting from a limited corpus of texts of French travelers in Persia in the nineteenth century.